Local Analogs of Potential Ionizers of the Intergalactic Medium: Compact Star-forming Galaxies with Intense C IV λ1550 Emission - Intae Jung; Swara Ravindranath; Anne E. Jaskot; Henry C. Ferguson; Bethan L. James (The Astrophysical Journal)
We performed spectroscopic analyses of five local compact star-forming galaxies (CSFGs) with extremely high [O iii ]/[O ii ] (O _32 ) ratios (>20). These targets remarkably share similar properties with high-redshift C iv emitters at z  > 6: high H β equivalent widths (EWs > 200Å), extreme O _32 ratios, low metallicities (12+log(O/H) ≲ 7.8), low C/O abundances (log(C/O) < −0.7), and high ionization conditions (log U  > −2). The ultraviolet (UV) spectra were acquired using the Hubble Space Telescope’s (HST) Cosmic Origins Spectrograph and Space Telescope Imaging Spectrograph. We have identified a wealth of rest-frame UV emission lines (C iv , He ii , O iii ], C iii ]) in the HST spectra. Notably, all our targets show intense C iv emission lines with rest-frame EWs > 10 Å, indicative of hard ionizing radiation. The rest-frame UV emission line diagnostics disfavor an active galactic nucelus and could be consistent with significant shock contributions to the source of ionizing radiation. Four of our targets show high C iv /C iii ] ratios (≥1.4), suggestive of strong Lyman-continuum leakage (LyC escape fraction, f _esc,LyC  > 10%) from these sources. This is consistent with their Ly α -inferred LyC escape fractions ( f _esc,LyC  = 9%–31%). We derive relative C/O abundances from our sources, showing log(C/O) values from −1.28 to −0.77, comparable to those of reionization-era galaxies at z  ≳ 6. The properties of the CSFGs, particularly their intense C iv emission and high O _32 ratios, which suggest significant LyC escape fractions, are similar to those of the reionization-era C iv emitters. These similarities reinforce the hypothesis that these CSFGs are the closest analogs of significant contributors to the reionization of the intergalactic medium.